2021
DOI: 10.1111/1440-1681.13541
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities after induction of endoplasmic reticulum stress are associated with mitochondrial dysfunction and connexin43 expression

Abstract: The endoplasmic reticulum (ER) is responsible for protein synthesis and calcium storage. ER stress, reflected by protein unfolding and calcium handling abnormalities, has been studied as a pathogenic factor in cardiovascular diseases. The aim of this study is to examine the effects of ER stress on mechanical and electrophysiological functions in the heart and explore the underlying molecular mechanisms. A total of 30 rats were randomly divided into control, ER stress inducer (tunicamycin[TN]) and ER stress inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Therefore, in zebrafish, the data confirmed that S1R activity is not a requisite to mitochondria physiology but appears necessary, as S1R invalidation resulted in a −26% decrease in basal respiration and −34% in the respiration related to the formation of ATP. Induction of ER stress by Tunicamycin resulted in significant alterations of the different parameters related to oxidative respiration, as previously observed [46,73,74] that were progressive and observed at shorter exposure times (2 h, 4 h, data not shown). Interestingly, loss of S1R abolished the decrease of basal and ATP-linked OCR after Tunicamycin treatment, suggesting that S1R was necessary for the adaptation of mitochondrial physiology to ER stress.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, in zebrafish, the data confirmed that S1R activity is not a requisite to mitochondria physiology but appears necessary, as S1R invalidation resulted in a −26% decrease in basal respiration and −34% in the respiration related to the formation of ATP. Induction of ER stress by Tunicamycin resulted in significant alterations of the different parameters related to oxidative respiration, as previously observed [46,73,74] that were progressive and observed at shorter exposure times (2 h, 4 h, data not shown). Interestingly, loss of S1R abolished the decrease of basal and ATP-linked OCR after Tunicamycin treatment, suggesting that S1R was necessary for the adaptation of mitochondrial physiology to ER stress.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Cx43 is detected within mitochondria isolated from stem cell antigen-1 + ( Lu et al, 2010 ) and H9c2 cells ( Tu et al, 2017 ; Pecoraro et al, 2021 ), from brown adipose tissue ( Kim et al, 2017 ), from astrocytes ( Kozoriz et al, 2010 ) and brain ( Azarashvili et al, 2011 ) as well as from liver ( Li et al, 2021 ). Most studies, however, focused on the mitochondrial localization of Cx43 in the heart ( Boengler et al, 2005 ; Gorbe et al, 2011 ; Srisakuldee et al, 2014 ; Shan et al, 2015 ; Gadicherla et al, 2017 ; Wang et al, 2019 ; He et al, 2021 ; Wei et al, 2022 ) including neonatal cardiomyocytes ( Tu et al, 2017 ) and embryonic stem cell-derived cardiomyocytes ( Wang et al, 2021 ). Mitochondria from mice with inducible Cx43 knockout ( Boengler et al, 2005 ; Gadicherla et al, 2017 ; Wang et al, 2019 ) or mice in which Cx43 was replaced by Cx32 ( Miro-Casas et al, 2009 ) served as respective negative controls.…”
Section: Presence Of Connexins Within Mitochondriamentioning
confidence: 99%
“…Mitochondrial quality control is mediated by a homeostatic balance between mitochondrial biogenesis and degradation, mainly regulated by dynamic processes such as mitochondrial fission and fusion, mitochondrial cristae remodeling, mitochondrial biosynthesis, Ca 2+ homeostasis, and mitophagy [ 15 ]. In various animal models, mitochondrial damage produces a large number of oxidative substances that lead to myocardial apoptosis, ultimately leading to remodeling of the atria [ 16 , 17 , 18 , 19 , 20 ] and/or ventricles [ 18 , 21 , 22 ], and decreased cardiac function. MFN2 is a mitochondrial fusion protein mainly involved in the fusion of mitochondria.…”
Section: Introductionmentioning
confidence: 99%